Upaya Hukum Pemegang Saham Minoritas Atas Perusahaan yang Melakukan Merger/Akuisi - Sudjai, Sudjai; Suanton, Suanton; Zubair, Asyhary (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2024)
Minority shareholders have the same rights as majority shareholders and are protected by Law Number 40 of 2007 concerning Limited Liability Companies, one of which is the right to determine the policy of the company that will make an acquisition or marger, but in practice we often read in print or in electronic media about lawsuits filed in the State High Court against majority shareholders because they feel aggrieved by shareholders majority. Therefore, the author examines the rights of minority shareholders and the efforts that can be taken using legal channels if in the acquisition process or company marger harms minority shareholders. This research uses normative or doctrinaire qualitative methods by examining the legal rules that apply to the law and the rules below, so as to obtain a conclusion about the rights and legal remedies that can be carried out by minority shareholders. The results showed that the rights for minority shareholders are to participate in the Minority General Meeting of Shareholders (GMS), the right to get dividends, and the right to conduct an Extraordinary General Meeting of Shareholders (EGMS) in accordance with a court order. Meanwhile, legal remedies that can be taken by minority shareholders if they feel aggrieved in the acquisition process or marger feel aggrieved are asking the company to buy shares owned at a fair price, filing a lawsuit with the directors and commissioners at the High District Court, and proposing the company to be dissolved through the General Meeting of Shareholders (GMS).